Blockade of CCL2/CCR2 Signaling Pathway Exerts Anti-Inflammatory Effects and Attenuates Gestational Diabetes Mellitus in a Genetic Mice Model - Qi, Xinying; Xing, Yanping; Wang, Xuezhen (Hormone and Metabolic Research, 2020)
The chemokine (C-C motif) ligand 2 (CCL2) and its receptor CCR2 are involved in gestational diabetes mellitus (GDM). The present study aims to explore the effects of CCL2 blocking on GDM. Serum CCL2, interleukin (IL)-6, and tumor necrosis factor (TNF)-α were determined in GDM patients and healthy volunteers. C57BL/KsJdb/+mouse was used as the GDM model and CCL2 antibody (αCCL2) was applied. Flow cytometry was applied to determine the frequency of macrophages. Quantitative reverse transcription PCR (RT-qPCR) and western blot were determined to detect the mRNA and protein expressions, respectively. Enzyme-linked immunosorbent assay (ELISA) was applied to determine the levels of inflammatory cytokines and serum insulin. Serum CCL2 was correlated with inﬂammatory cytokines (IL-6 and TNF-α) in the GDM patients. Besides, the results showed high expressions of CCL2 in the visceral adipose tissue (VAT) and placenta tissue in the GDM mice. Flow cytometry and immunohistochemistry (IHC) staining showed the accumulations of macrophages in these tissues. Treatment of αCCL2 attenuated the GDM symptoms and ameliorated the inflammation. Furthermore, the treatment of αCCL2 improved reproductive outcomes in the GDM mice. Blockade of CCL2 attenuated GDM symptoms and reduced inflammatory cytokines in a genetic mice model.
Keywords: gestational diabetes mellitus, diabetes; inflammation; inflammatory cytokines; CCL2; CCR2